1980
DOI: 10.1177/0044118x8001200105
|View full text |Cite
|
Sign up to set email alerts
|

Developing Attitudes Toward the Role of Women

Abstract: In recent years, researchers have examined changes in attitudes toward the role of women, both among adults (Mason et al., 1976;Erskine, 1971;Ferree, 1974) and among college students (Parelius, 1975) and adolescents (Bush et al., 1977). Some have compared the attitudes of men and women (Osmond and Martin, 1975; Steinmann and Fox, 1970); others have examined the relationship of attitudes to demographic variables such as employment status, educational attainment (Mason and Bumpass, 1975) and academic field of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1981
1981
1987
1987

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Less is known specifically about the relationship feminists have had with their parents. Jean Stockard (1980) found, however, using scores on a feminism scale (Acker, Grether, Ewart-Tonkinson, Naffziger, Peterson, Skold, Silviera, & Stockard, 1974) as her measure, that more feminist college women reported "worse" relations with their fathers in high school than did more traditional women. She also found that feminists reported less similarity to and less frequent associations with the mother than nonfeminists and that both parents had more nontraditional sex-role related attitudes than those reported by the more traditional young women in the sample.…”
Section: Parental Relations and Sex-role Attitudesmentioning
confidence: 99%
See 2 more Smart Citations
“…Less is known specifically about the relationship feminists have had with their parents. Jean Stockard (1980) found, however, using scores on a feminism scale (Acker, Grether, Ewart-Tonkinson, Naffziger, Peterson, Skold, Silviera, & Stockard, 1974) as her measure, that more feminist college women reported "worse" relations with their fathers in high school than did more traditional women. She also found that feminists reported less similarity to and less frequent associations with the mother than nonfeminists and that both parents had more nontraditional sex-role related attitudes than those reported by the more traditional young women in the sample.…”
Section: Parental Relations and Sex-role Attitudesmentioning
confidence: 99%
“…and respect for the daughter. Previous work on parental influences on sex-role related attitudes of college students has suggested that women who are more traditional in their attitudes Women's Perceptions of Their Parents s have fathers who are seen not only as "close" to them (Stockard, 1974(Stockard, , 1980 but also as very protective of them, and who do not encourage their being independent and who do not take them very seriously or respect them (Johnson, 1955(Johnson, , 1963. In terms of the present study, we hypothesized that heterosexual traditional women would report more protection from their fathers and less independence granting and respect than would feminist women.…”
Section: Specific Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Women tend toward more liberal attitudes than men (Albrecht et Geerken and Gove, 1983;Cherlin and Walters, 1981;Osmond and Martin, 1975;Martin et al, 1980;Stockard, 1980;Tomeh, 1980;Thornton et al, 1983;Herzog et al, 1983).…”
mentioning
confidence: 99%